2008
DOI: 10.1111/j.1574-6968.2007.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional profiles ofStaphylococcus aureustreated with berberine chloride

Abstract: In this study, we show that berberine chloride (BBR) has antimicrobial activities against all 43 tested strains of Staphylococcus aureus, an important human and animal pathogen. However, the response mechanisms of S. aureus to BBR are still poorly understood. Affymetrix GeneChips were used to determine the global transcription of S. aureus triggered by treatment with subinhibitory concentrations of BBR. 468 genes were up-regulated and 262 genes were down-regulated upon exposure to BBR. There was elevated trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 35 publications
(48 reference statements)
2
51
0
Order By: Relevance
“…All samples were analyzed in triplicate and normalized against 16S rRNA gene expression. RT-PCR was performed in triplicate using the 7000 Sequence Detection System (Applied Biosystems, USA) according to a previously described procedure (Wang et al, 2008).…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…All samples were analyzed in triplicate and normalized against 16S rRNA gene expression. RT-PCR was performed in triplicate using the 7000 Sequence Detection System (Applied Biosystems, USA) according to a previously described procedure (Wang et al, 2008).…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…Although possessing a variety of pharmacological effects including antidiabetic, anti-hyperlipidemic, antimicrobial, anti-inflammatory, and antioxidant activities, berberine has long been used mainly as an agent against gastroenteritis, dysentery, and abdominal pain [2]. Several reports have showed that its anti-gastroenteritic and anti-dysenteric effects are largely attributed to its direct antimicrobial effect on bacterial pathogens [3–7]. However, it is unknown whether berberine has potentiated the bacterial killing ability of the host's phagocytes including macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…This could be associated with the antimicrobial property of berberine since adhesion to the tissue surface is the first step for bacteria to establish infection. Unfortunately, they observed that E. coli growth was reduced by only 10% in the presence of 300 μg/mL berberine chloride, although 90% of its ability to adhere was lost (Wang et al 2008). Stermitz et al (2000) reported that berberine is pumped out by bacterial multi-drug resistance (MDR) pumps.…”
Section: Discussionmentioning
confidence: 98%